Promoting Students’ Critical Thinking in Writing Persuasive Text through Explicit Direct Instruction (Edi) - Susilawati Susilawati; Audi Yundayani; Chairunnisa Chairunnisa (Journal of English Language Studies, 2019)
Critical thinking is regarded as a critical issue to solve. Students should be equipped by critical thinking due to its pivotal position in developing students’ language competence. However, this issue remains unsolved for many obstacles occurring at classroom learning. Explicit Direct Instruction (EDI) is claimed as one of the methods contributing to successful critical thinking development. The present research aimed at portraying how EDI directed students to enhance their critical thinking and EDI implementation in writing persuasive essay. The present research employed qualitative approach with case study method. The subjects involved in this research were 20 of 3rd-year students of a private college in East Jakarta. The instruments used to collect the data were observation, interview, and document analysis. The findings of the research indicated that: 1) EDI assisted the students with the promotion of their critical thinking in the argument analysis by the reinforcement provided by re-teaching and CFU with T-APPLE concept, and 2) EDI was implemented based on the seven components of its lesson design and in conjunction with a variety of learning strategies. To these extents, EDI implementation in writing class has  specifically enlighten one of critical writing dimensions. Research on EDI effectiveness quantitatively is adjured.